-4+7q=8q-7-3

Simple and best practice solution for -4+7q=8q-7-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4+7q=8q-7-3 equation:


Simplifying
-4 + 7q = 8q + -7 + -3

Reorder the terms:
-4 + 7q = -7 + -3 + 8q

Combine like terms: -7 + -3 = -10
-4 + 7q = -10 + 8q

Solving
-4 + 7q = -10 + 8q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-8q' to each side of the equation.
-4 + 7q + -8q = -10 + 8q + -8q

Combine like terms: 7q + -8q = -1q
-4 + -1q = -10 + 8q + -8q

Combine like terms: 8q + -8q = 0
-4 + -1q = -10 + 0
-4 + -1q = -10

Add '4' to each side of the equation.
-4 + 4 + -1q = -10 + 4

Combine like terms: -4 + 4 = 0
0 + -1q = -10 + 4
-1q = -10 + 4

Combine like terms: -10 + 4 = -6
-1q = -6

Divide each side by '-1'.
q = 6

Simplifying
q = 6

See similar equations:

| 0.5k+1.5=3 | | -4-t=-4+t | | 3x+7=7x+15 | | 15/6=n/12 | | 0.6x+2=0.7+2 | | -10-7w-10=7-4w | | 4-3cot=1 | | 40=8(x-8) | | X^2-12X-4.5=0 | | P=2x+3 | | -8y=-6-9y | | -3(5+2x)=-2x+13 | | 8-(4x-12)=8x-(3x-2) | | 2-5f=-7f+10 | | 4+2y=10-4y | | 3/5=6n | | -j=j-8 | | -5x(4x-8y^2+4)= | | 10-6n=-6-10n | | 3b-11=3+b | | 7x-14=7(x+4) | | 5+10d=9d | | 6x-(10-2x)=3x+5 | | 9b+3=22 | | 18.9125-(1/4)= | | 9b+3=20 | | 9b+3=19 | | 2x^3-11x^2-10x+75=0 | | 9b+3=18 | | 9b+3=16 | | 4(t-3)+6t=5(2t+5)-12 | | 4x+3(2x-1)-4x=x |

Equations solver categories